Biochemical study of diabetic wound treated with Malaysian gelam honey - Samedrik, Fatin Sarahani (2016)
Impaired wound healing is a major complication of diabetes mellitus. Existing treatments of diabetic wounds are not very effective and it is essential to find other economical alternative to treat diabetic wound. This study aims to evaluate the biochemical changes in diabetic wound after treated with topical application of Gelam honey. The efficacy of topical application of Gelam honey in treating diabetic wound was evaluated in 48 male Sprague-Dawley rats. The rats were randomly divided into four groups of six rats in each group. 3 cm full-thickness incision wound was performed on the left and right side of the rat's dorsum. Gelam honey was applied approximately half an hour post-wounding. On day 1 and day 14 post wounding, six rats from each group were euthanized and the skin samples were taken for biochemical analyses. The biochemical analyses were conducted to estimate the concentration of collagen, hexosamine, protein and uronic acid in the granulation tissue. The biochemical analyses demonstrated higher content of the tested parameters in the diabetic wound treated with Gelam honey as compared to the untreated diabetic wound and diabetic wound treated with silver sulphadiazine. The results of this study showed that Gelam honey has the potential to enhance diabetic wound healing and can be recommended as an alternative in treating diabetic wound.